Experimental Investigation of VOCs Emitted from a DI-CI Engine Fuelled with Biodiesel, Diesel and Biodiesel-Diesel Blend: VOCs from a Di-Ci Engine - Shahab, Asad Naeem; shan, G. E. Yun-; wei, Tan Jian-; hua, Liu Zhi- (Biological Sciences - PJSIR, 2009)
Experimental investigation of volatile organic compounds (VOCs) emitted by a turbocharged direct injection compression ignition (DI-CI) engine, alternatively fuelled with biodiesel and its 20% blend with diesel, revealed dominancy of diesel and biodiesel in aromatic hydrocarbons, esters other oxides, respectively, in total volatile organic compounds (TVOCs). The overall brake specific emission of VOCs increased at rated speed compared to maximum torque speed. The VOCs exhibited their maxima at low load, and minima at medium load for diesel and B100. Engines with a speed of 2300 r/min and 100% load showed a reduction in BTX emissions from B20 and B100, as compared to diesel. The sum of VOC-components of B20 and B100 reduced as compared to that of the diesel, for all the engine conditions. The mean BSE of BTX-components taken from all the engine conditions decreased with B20 and B100, relative to fossil diesel.